ANALISIS PRAKTIK MANAJEMEN LABA ANTARA PERUSAHAAN TERBUKA SEKTOR MANUFAKTUR PADA NEGARA PENGADOPSI DAN NON-PENGADOPSI IFRS YANG DIPROYEKSIKAN OLEH THAILAND DAN INDONESIA - , DITO DIDI ADIKTA, Prof. Dr. Jogiyanto Hartono M., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to determine whether accounting standard and policy have impact to earning management practice in manufacturing companies listed in Indonesia Stock Exchange and The Thailand Stock Exchange. Specifically, the purpose of this research is to determine whether IFRS adoption, asset turnover, & market capitalization have impact to earning management practice. Manufacturing sector is selected due to market circumstances within observation period occurred a phenomenon worth observed This research uses binary logistic regression with accounting standard as dependent variable, as well as asset turnover and market capitalization as independent variables. The observation period range from year 2007-2012 with sample of 45 manufacturing companies listed n Indonesia Stock Exchange and 77 manufacturing companies listed in The Stock Exchange of Thailand. Judgment sampling is chosen as sample selection method The result of this research shows there are significant positive between accounting standard toward earning management, also significant negative correlation between asset turnover and market capitalization toward earning management.